Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"-- Author's abstract

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.